Drying rate analysis of three fish species dried using an amendedbiomass (charcoal) dryer - Gaydaybu, James Flomo; Anaka, Bill; Hime, Elijah A; Okeme, Coolaid I Obaham; Ndaloma, Philip G S; Achimba, Orseer (Journal of Postharvest Technology, 2021)
This study was on improved design and development of a convectional biomass (charcoal) fish dryer. The dimension of the dryer was 600 mm x 600 mm x 800 mm with a truncated pyramid connecting duct that conveyed and dispersed hot air over trays. The dryer was evaluated by drying Nile Tilapia, Giraffe Catfish, and Mud Catfish. The data were analyzed using, Statistical Package for Social sciences (SPSS) version 25.The Nile Tilapia moisture content was reduced from 77.13 to 12.98% wb for six hours, the Giraffe Catfish moisture content was reduced from 79.31 to 13.26% wb for six hours while the Mud Catfish moisture was also reduced from 81.07 to 13.25% wb for eight hours. The charcoal was fed into the charcoal chamber as one Kg per hour with a maximum temperature of 130oC. The maximum drying rate was 134 g/h recorded during the Giraffe Catfish drying. The sun-drying took 26 hours to reduce the moisture content of Nile Tilapia from 77.34 to 22.06% wb, the Giraffe Catfish moisture content was reduced from 78.86 to 26. 08% wb while the Mud Catfish moisture content was also reducing from 81.03 to 31.26% wb.